Incidence of teaching strategies in the teaching and learning of mathematics on the academic performance of students of the Unified General Baccalaureate of the “Matilde Hidalgo de Procel” Educational Unit - Betancourt Vera, Karla Johanna; Cordero de Jiménez, Yoskira Naylett (SATHIRI, 2024)
In the last two decades of the 21st century, there is a pending educational agenda to improve the classroom experience regarding: the limited communication between teacher and student, only expository classes, the role of students as passive recipients of information, higher scores for memorization of concepts and formulas, poor application of knowledge, among others. The objective of this research is to analyze the impact on academic performance when applying didactic strategies of Problem-Based Learning (PBL) in the teaching and learning of mathematics of students of the Unified General Baccalaureate of the “Matilde Hidalgo de Procel” Educational Unit”. The research paradigm is quantitative, field, and transversal, and the sample was the third year high school course, made up of 50 students. The results are obtained from the application of a pre-test and a post-test, that is, without PBL and with PBL respectively. Among the results, a slight increase in academic performance is evident on average when the PBL methodology is applied. A hypothesis test was carried out and the result was statistically significant, rejecting the null hypothesis. In conclusion, statistically the difference is significant between both teaching methodologies for the specific topic of mathematics and the teacher’s experience has been favorable in extending the classes in an application manner. For the students it has been representative for evidencing the usefulness of the topic, applying the content to make a proposal in project format.